D-Dimer Is Associated With Coronary Microvascular Dysfunction in Patients With Non-obstructive Coronary Artery Disease and Preserved Ejection Fraction - Lin, Yan; Hu, Xiangming; Wang, Weimian; Yu, Bingyan; Zhou, Langping; Zhou, Yingling; Li, Guang; Dong, Haojian (Frontiers in Cardiovascular Medicine, 2022)
Background. Coronary microvascular dysfunction (CMVD), as an important etiology of ischemic heart disease, has been widely studied. D-dimer is a simple indicator of microthrombosis and inflammation. However, whether an increase in D-dimer is related to CMVD is still unclear. Materials and Methods. This was a retrospective study consecutively enrolled patients with myocardial ischemia and excluded those with obstructive coronary artery. D-dimer was measured at admission and TIMI myocardial perfusion grade (TMPG) was used to distinguish CMVD. Patients was divided into two groups according to whether the D-dimer was elevated (>500 ng/mL). Logistic models and restricted cubic splines were used to explore the relationship between elevated D-dimer and CMVD. Results. A total of 377 patients were eventually enrolled in the study. Of these, 94 (24.9%) patients with CMVD had older age and higher D-dimer levels than those without CMVD. After full adjustment for other potential clinical risk factors, patients with high D-dimer levels (>500 ng/mL) had a 1.89-times (95% confidence interval: 1.09-3.27) higher risk of CMVD than patients with low D-dimer levels. A nonlinear relationship was found between concentrations of D-dimer and CMVD. With increased D-dimer level, the incidence of CMVD increased and then remained at a high level. Stratified analysis was performed and showed similar results. Conclusions. Elevated D-dimer level is associated with the incidence of CMVD and potentially serve as a simple biomarker to facilitate diagnosis of CMVD for patients with angina.